Insulin resistance: a new consequence of altered carotid body chemoreflex? - Conde, Silvia V. (J Physiol, 2016)
Metabolic diseases affect millions of individuals across the world and represent a group of chronic diseases of very high prevalence and relatively low therapeutic success, making them suitable candidates for pathophysiological studies. The sympathetic nervous system (SNS) contributes to the regulation of energy balance and energy expenditure both in physiological and pathological states. For instance, drugs that stimulate sympathetic activity decrease food intake, increase resting metabolic rate and increase the thermogenic response to food, while pharmacological blockade of the SNS has opposite effects. Likewise, dysmetabolic features such as insulin resistance, dyslipidaemia and obesity are characterized by a basal overactivation of the SNS. Recently, a new line of research linking the SNS to metabolic diseases has emerged with the report that the carotid bodies (CBs) are involved in the development of insulin resistance. The CBs are arterial chemoreceptors that classically sense changes in arterial blood O(2), CO(2) and pH levels and whose activity is known to be increased in rodent models of insulin resistance. We have shown that selective bilateral resection of the nerve of the CB, the carotid sinus nerve (CSN), totally prevents diet‐induced insulin resistance, hyperglycaemia, dyslipidaemia, hypertension and sympathoadrenal overactivity. These results imply that the beneficial effects of CSN resection on insulin action and glucoregulation are modulated by target‐related efferent sympathetic nerves through a reflex that is initiated in the CBs. It also highlights modulation of CB activity as a putative future therapeutic intervention for metabolic diseases. [Image: see text]